OS2.4 Angiotensin II Receptor Blockers, steroids and radiotherapy in glioblastoma - A randomized multicenter trial (ASTER Trial). An ANOCEF Study. (19th September 2018) - URSU, R; Thomas, L; Psimaras, D; Chinot, O; Le Rhun, E; Ricard, D; Charissoux, M; Cuzzubbo, S; Sejalon, F; Quillien, V; Hoang-Xuan, K; Ducray, F; et al.
Abstract: Background: Glioblastomas, the most common primary central nervous system tumors, induce a peritumoral vasogenic edema impairing functional status and quality of life. Steroids reduce brain tumor-related edema, but are associated with numerous side effects. It was reported in a retrospective series that angiotensin receptor blockers (ARBs) might be associated with reduced peritumoral edema. The ASTER study is a randomized, placebo-controlled trial to assess whether or not the addition of Losartan to standard of care can reduce steroid requirement during radiotherapy in patients with newly diagnosed glioblastoma. Material and Methods: Patients with a histologically confirmed newly diagnosed glioblastoma after biopsy or partial surgical resection were randomized between Losartan or placebo in addition to standard of care (SOC) with radiotherapy (RT) and temozolomide (TMZ). The primary objective was to investigate the steroid dosage required to control brain edema on the last day of RT in each arm. The secondary outcomes were steroids dosage 1 month after the end of RT, assessment of cerebral edema on MRI, tolerance, and survival. Results: Seventy five (75) patients were randomly assigned to receive Losartan (37 patients) or placebo (38 patients). No difference in the steroid dosage required to control brain edema on the last day of radiotherapy, or one month after completion of RT, was seen between both arms. A trend towards reduction of peritumoral edema over time was seen on MRI, but this reduction did not reach statistical significance. Median OS was similar in both arms. Conclusion: Losartan, although well tolerated, does not reduce the steroid requirement in newly diagnosed GBM patients treated with concomitant radiotherapy and temozolomide.